(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the safety and corneal endothelial protective efficacy of a mannitol-containing ophthalmic viscosurgical device during phacoemulsification for cataract surgery in patients with low corneal endothelial cell density. Methods: This randomized controlled trial included cataract patients indicated for phacoemulsification with preoperative endothelial cell density ranging from 1000 to 2000 cells/mm² at Saigon Vinh Eye Hospital from October 2024 to May 2025. Patients were randomly assigned to three groups: group A received an ophthalmic viscosurgical device containing 2% sodium hyaluronate combined with 0.5% mannitol; group B received an ophthalmic viscosurgical device containing 1.4% sodium hyaluronate; and group C received an ophthalmic viscosurgical device containing 2.4% hydroxypropyl methylcellulose. Endothelial cell density and morphology, central corneal thickness, and best-corrected visual acuity were assessed preoperatively and at 1 week, 1 month, and 3 months postoperatively. Results: At 1 week postoperatively, group A demonstrated significantly higher endothelial cell density, lower coefficient of variation, higher percentage of hexagonal cells, and lower central corneal thickness compared with the other two groups (p < 0.05). Postoperative visual acuity improved more markedly in group A. By 1 month, corneal edema had largely resolved in all groups, and intergroup differences in visual acuity were no longer statistically significant. Conclusions: Ophthalmic viscosurgical device containing sodium hyaluronate 2% and mannitol 0.5% provides superior corneal endothelial protection during phacoemulsification in patients with low preoperative endothelial cell density, contributing to reduced postoperative corneal edema and faster early visual recovery postoperatively